2013
DOI: 10.1038/nature12294
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of allostery by protein intrinsic disorder

Abstract: Allostery is an intrinsic property of many globular proteins and enzymes that is indispensable for cellular regulatory and feedback mechanisms. Recent theoretical1 and empirical2 observations indicate that allostery is also manifest in intrinsically disordered proteins (IDPs), which account for a significant proportion of the proteome3,4. Many IDPs are promiscuous binders that interact with multiple partners and frequently function as molecular hubs in protein interaction networks. The adenovirus early region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
293
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(297 citation statements)
references
References 31 publications
(52 reference statements)
2
293
1
1
Order By: Relevance
“…There has recently been growing interest in the regulation of protein functions in an allosteric manner 19,25,[28][29][30][31][32] . However, the operational mechanism of the allosteric regulation remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…There has recently been growing interest in the regulation of protein functions in an allosteric manner 19,25,[28][29][30][31][32] . However, the operational mechanism of the allosteric regulation remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…IDRs such as the SF3b155 ULM-containing region often coordinate the synergistic action of multiple weak binding sites to modulate positive or negative allostery, as recently exemplified for coordination of host CBP or pRB proteins by the adenoviral protein E1A (Ferreon et al 2013). The ULM-containing region of SF3b155 adjoins its binding site for p14, an RRM-like U2 snRNP subunit that ultimately contacts the branch point sequence of the pre-mRNA Cass and Berglund 2006;Schellenberg et al 2006;Spadaccini et al 2006).…”
Section: Potential Functions Of Multiple Functions Of Multiple Sf3b15mentioning
confidence: 99%
“…This improves the affinity of the second binding event (because binding need no longer pay the unfavorable cost associated with folding), leading to positive allosteric behavior. Ferreon et al (24), for example, have shown that the intrinsically disordered oncoprotein adenovirus early region 1A (E1A) folds upon binding either of its two (different) target ligands (CREB binding protein or retinoblastoma protein), thus increasing the affinity with which the second ligand binds and rendering the system heterotropically allosteric. In addition, Furukawa et al (25) have shown that the partially intrinsically disordered protein STIM 1 exhibits strongly homotropic allosteric binding to calcium.…”
mentioning
confidence: 99%
“…Specifically, both theoretical (23) and experimental (24,25) studies have demonstrated that the global conformation change these proteins undergo upon an initial ligand binding event provides a convenient means of preorganizing a second, distal ligand binding site. This improves the affinity of the second binding event (because binding need no longer pay the unfavorable cost associated with folding), leading to positive allosteric behavior.…”
mentioning
confidence: 99%